Maternal nutrition intervention and maternal complications in 4 districts of Bangladesh: a nested cross-sectional study - Todd, Catherine S.; Chowdhury, Zakaria; Mahmud, Zeba; Islam, Nazia; Shabnam, Sadia; Parvin, Musarrat; Bernholc, Alissa; Martinez, Andres; Aktar, Bachera; Afsana, Kaosar; Sanghvi, Tina (PLOS Medicine, 2022)
This article was published in The Plos Medicine [© 2019 Todd et al. This is an open access article distributed under the terms of the Creative Commons Attribution License] and the definite version is available at: https://doi.org/10.1371/journal.pmed.1002927. The Journal's website is at: https://journals.plos.org/plosmedicine/article?id=10.1371/journal.pmed.1002927